Tanggung Jawab Pendidikan Islam (Orang Tua, Guru Dan Masyarakat) - Muhammedi Muhammedi (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
According to the Quran, the Islamic educational responsibilities dalah duty of parents, educators/teachers and communities, each of which has an important role in reciprocation of education. parents must provide education including the education of faith, morals, physical, intellectual, psychological, social, and sexual. Educators/teachers have the responsibility in the education of them became teachers, educators, and leaders. The responsibility of society is to become a controller for the continuity of education and in this case the most central control of education is the leader or the government, which should provide direction and help to achieve the educational goals.